Elevated levels of Letm1 drives mitochondrial dysfunction and cardiomyocyte stress-mediated apoptosis in cultured cardiomyocytes - Deshpande, Anushka; Weirauch, Leo; Baral, Tapan Kumar; Steier, Marco; Borlepawar, Ankush; Kumari, Manju; Kilian, Lucia S.; Richter, Karsten; Hammer, Elke; Frank, Derk; Schmidt, Constanze; Frey, Norbert; et al. (Cell communication and signaling, 2025)
Cardiac ischemia, a predominant cause of heart failure, is marked by profound mitochondrial dysfunction, dysregulated ion homeostasis, and maladaptive cellular remodeling, all of which compromise cardiac performance. The mitochondrial inner membrane protein Leucine zipper-EF-hand containing Transmembrane Protein 1 (Letm1), implicated in Wolf-Hirschhorn Syndrome, is essential for mitochondrial function. Although genetic alterations in Letm1 are linked to cardiomyopathies, its specific contributions to cardiac pathophysiology, particularly in the context of ischemic heart disease, remain poorly defined. This study aims to elucidate the role of Letm1 in ischemic cardiac pathology and its mechanistic impact on cardiomyocyte function.
Online veröffentlicht: 23. August 2025
Gesehen am 12.01.2026